Biographical trajectories and parenting projects of same-sex couples - Santos, F. (2018)
Based on qualitative interviews with Portuguese non-heterosexuals young men and woman living in conjugality, the article aims to analyses their biographical trajectories and parenting projects. The findings reveal that the main obstacles to the conception and implementation of the parenting projects for same-sex couples are the internalized homophobia; the «drama» that is still the revelation of the non-heteronormative sexuality to close relatives; ideal norms and representations about male and female social roles, mainly the motherhood ideology. Despite the recent legal changes about the same-sex marriage and same-sex adoption in Portugal, others structural constraints such as the work precariousness of the Portuguese young adults have also a negative and a cumulative effect on the transition to parenthood for non-heterosexuals men and woman.